2007
DOI: 10.1007/s11172-007-0155-4
|View full text |Cite
|
Sign up to set email alerts
|

New synthesis of benzo[b][1,6]naphthyridines and pyrido[4,3-b]benz[f]azepines from lactim ethers of 3,4-dihydrocarbostyril and 1H-2,3,4,5-tetrahydrobenz[b]azepin-2-one

Abstract: New synthesis of benzo[b][1,6]naphthyridines and pyrido[4,3 b]benz[ f ]azepines from lactim ethers of 3,4 dihydrocarbostyril and 1H 2,3,4,5 tetrahydrobenz[b]azepin 2 oneCondensation of lactim ethers of 3,4 dihydrocarbostyril and 1H 2,3,4,5 tetrahydro benz[b]azepin 2 one with malonodinitrile, cyanoacetamide, and ethyl cyanoacetate gave the corresponding 2 methylidene derivatives. Their reactions with dimethylformamide diethyl acetal followed by cyclization into benzo[b][1,6]naphthyridines and pyrido[4,3 b]benz[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…1 Recently, we have shown that 3,4 dihydro сarbоstyryl and 1H 2,3,4,5 tetrahydrobenz[b]azepin 2 one lactim ethers smoothly reaсt with сyanoaсetiс aсid derivatives to form the сorresponding methylidene de rivatives, whiсh turned out to be convenient starting сompounds for the synthesis of triсyсliс systems, сont aining hydrogenated naphthiridine and pyridoazepine bi cyclic fragments. 2 It seemed interesting to apply this method for the synthesis of tri and tetraсyсliс indole сontaining deriva tives. A complexity of this pathway consisted in the fact that its realization required lactim ether of indolin 2 one (oxindole).…”
mentioning
confidence: 99%
“…1 Recently, we have shown that 3,4 dihydro сarbоstyryl and 1H 2,3,4,5 tetrahydrobenz[b]azepin 2 one lactim ethers smoothly reaсt with сyanoaсetiс aсid derivatives to form the сorresponding methylidene de rivatives, whiсh turned out to be convenient starting сompounds for the synthesis of triсyсliс systems, сont aining hydrogenated naphthiridine and pyridoazepine bi cyclic fragments. 2 It seemed interesting to apply this method for the synthesis of tri and tetraсyсliс indole сontaining deriva tives. A complexity of this pathway consisted in the fact that its realization required lactim ether of indolin 2 one (oxindole).…”
mentioning
confidence: 99%